Associations between social support and physical activity in postpartum: a Norwegian multi-ethnic cohort study - Karin Elisabeth Bennetter; Kåre Rønn Richardsen; Nina Køpke Vøllestad; Anne Karen Jenum; Hilde Stendal Robinson; Ibrahimu Mdala; Christin Wiegels Waage (BMC, 2023)
Background Social support is associated with higher self-reported physical activity (PA) in postpartum women, but it is unknown if similar association occur when using objective PA data. The aim was to explore the associations between social support and objectively recorded moderate-to-vigorous physical activity (MVPA) postpartum, and if associations differed across ethnic groups. Methods We used data from 636 women who participated in the STORK Groruddalen cohort study (2008-2010). MVPA minutes/day in bouts of ≥ 10 minutes was recorded by SenseWear Armband™ Pro3 (SWA) over 7 days, 14 weeks postpartum. Social support for PA from family or friends was measured by a modified 12-item version of the Social Support for Exercise Scale. We used single items, family support mean score (6 items) and friends' support mean score (6-items) in four separate count models, and adjusted for SWA week, age, ethnicity, education, parity, body mass index and time since birth. We tested interactions between social support and ethnicity. Analyses were performed on complete cases and imputed data. Results Based on imputed data, we observed that women who reported low and high support from family accumulated 16.2 (IQR: 6.1-39.1) and 18.6 (IQR: 5.0-46.5) MVPA minutes/day, respectively. Women who reported low and high support from friends accumulated 18.7 (IQR: 5.9-43.6) and 16.8 (IQR: 5.0-45.8) MVPA minutes/day. We observed a 12% increase in MVPA minutes/day for each additional increase in mean family support score (IRR = 1.12, 95% CI: 1.02 to 1.25). Women reporting high level of support from family on 'discuss PA', 'co-participation' and 'take over chores' accumulated 33%, 37% and 25% more MVPA minutes/day than women reporting low level of support respectively ('discuss PA': IRR = 1.33, 95% CI: 1.03 to 1.72, 'co-participation': IRR = 1.37, 95% CI: 1.13 to 1.66 and 'take over chores': IRR = 1.25, 95% CI: 1.02 to 1.54). Associations were not modified by ethnicity. No statistically significant association between support from friends and MVPA was observed. Similar results were found in complete case analyses, with a few exceptions. Conclusion Overall family support and specific forms of support from family were associated with MVPA across ethnic groups, while support from friends was not associated with MVPA postpartum.